2024
DOI: 10.1177/09636897241245796
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Exploration on the Immunoregulation of Allogeneic Heart Transplantation Rejection in Rats With Exosome miRNA and Proteins From Overexpressed IDO1 BMSCs

Rui Zheng,
Xinxin Wu,
Si Li
et al.

Abstract: Immunoregulation and indoleamine 2,3-dioxygenase 1 (IDO1) play pivotal roles in the rejection of allogeneic organ transplantation. This study aims to elucidate the immune-related functional mechanisms of exosomes (Exos) derived from bone marrow–derived mesenchymal stem cells (BMSCs) overexpressing IDO1 in the context of allogeneic heart transplantation (HTx) rejection. A rat model of allogeneic HTx was established. Exos were extracted after transfection with oe-IDO1 and oe-NC from rat BMSCs. Exos were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Human umbilical cord-derived MSCs alleviated myocardial fibrosis and restored miRNA-133a expression in diabetic cardiomyopathy, which positively influenced fibrosis markers and inflammatory mediators in a diabetic mouse model [79]. Additionally, the immunoregulatory properties of exosomal miRNAs from bone marrow MSCs overexpressing IDO1 demonstrated their potential to modulate immune responses and improve allogeneic heart transplantation outcomes by influencing key immune-related proteins and miRNAs [80]. Zhu et al [81] reported that suppressing miR-873-5p rejuvenates aging MSCs, enhancing their functionality and therapeutic efficacy for myocardial infarction repair through modulating autophagy via the AMPK signaling pathway.…”
Section: Extracellular Vesicles and Secretomementioning
confidence: 98%
“…Human umbilical cord-derived MSCs alleviated myocardial fibrosis and restored miRNA-133a expression in diabetic cardiomyopathy, which positively influenced fibrosis markers and inflammatory mediators in a diabetic mouse model [79]. Additionally, the immunoregulatory properties of exosomal miRNAs from bone marrow MSCs overexpressing IDO1 demonstrated their potential to modulate immune responses and improve allogeneic heart transplantation outcomes by influencing key immune-related proteins and miRNAs [80]. Zhu et al [81] reported that suppressing miR-873-5p rejuvenates aging MSCs, enhancing their functionality and therapeutic efficacy for myocardial infarction repair through modulating autophagy via the AMPK signaling pathway.…”
Section: Extracellular Vesicles and Secretomementioning
confidence: 98%